1991
DOI: 10.1093/infdis/164.6.1173
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Intraabdominal Abscess Formation: Abscess-Potentiating Agents and Inhibition of Complement-Dependent Opsonization of Abscess-Inducing Bacteria

Abstract: Bacteroides fragilis and Escherichia coli are synergistic in the production of intraabdominal abscesses. However, these bacteria initiate abscess formation only when inoculated with an agent such as autoclaved colonic contents (ACC) or bran (a fiber analogue). The mechanism of action of the abscess-potentiating agent was studied. Opsonins in normal mouse serum were determined for phagocytic killing by murine neutrophils of B. fragilis and E. coli. Opsonization required fixation of complement by the alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In human IAC, perforation or leakage of the GI tract is commonly associated with abscess formation but abscesses rarely result from infected peritoneal catheters. Sterile feces potentiates intra-abdominal infections by depleting complement-derived opsonins and impairing phagocytic killing (27,28). These effects likely account for our observation that tissue burdens and persistence of C. glabrata were increased in the presence of sterile feces, despite greater neutrophil counts.…”
Section: Ndmentioning
confidence: 78%
“…In human IAC, perforation or leakage of the GI tract is commonly associated with abscess formation but abscesses rarely result from infected peritoneal catheters. Sterile feces potentiates intra-abdominal infections by depleting complement-derived opsonins and impairing phagocytic killing (27,28). These effects likely account for our observation that tissue burdens and persistence of C. glabrata were increased in the presence of sterile feces, despite greater neutrophil counts.…”
Section: Ndmentioning
confidence: 78%
“…These data give evidence that, along with the genetic differences in these isolates (34), functional and/or antigenic differences involved in lesion induction are present. PDD spirochetes induce abscess formation in this model without the need for potentiating agents, as needed in experiments with Bacteroides fragilis and Escherichia coli (15). It was found that the potentiating agent used in those experiments interfered with complement activation and opsonization of the bacteria, allowing B. fragilis and E. coli to persist and initiate abscess formation.…”
Section: Discussionmentioning
confidence: 93%
“…"~ Specific combinations of facultatively and obligately anaerobic bacteria, e.g., Escherichia coli and Bacteroides fragilis, on the other hand often resulted in abscess formation when clinically " significant " inocula were used, whether combined with adjuvant or n~t .~-~ In the case of the fibrin clot model, originally described by Ahrenholz and Simmons,' the only '' adjuvant " required with E. coli and B. fragilis was fibrinogen. [2][3][4][5][6][7][8][9][10] In the present study this rat fibrin clot model was used to produce intra-abdominal abscesses. Previous work had shown that persistent abscesses formed when both E. coli and B. fragilis were present," but, individually, either B. fragilis or E. coli was cleared from the peritoneal cavity within 48 h and 2 weeks respectively.…”
Section: Introductionmentioning
confidence: 99%